PERAN SANKSI PAJAK DALAM MEMBENTUK PERILAKU WAJIB PAJAK PADA UMKM: STUDI LITERATUR REVIEW - Erin Widianti (CV. Denasya Smart Publisher, 2025)
This This study systematically reviews the impact of tax sanctions and other influencing factors on tax compliance behavior among Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Through a Systematic Literature Review (SLR) of six empirical studies published between 2021–2025, the analysis reveals that tax sanctions significantly enhance compliance, but their effectiveness depends on mediating variables such as tax literacy, perceptions of fairness, and the quality of tax services. Key findings indicate that while sanctions positively influence compliance, their impact is diminished without adequate taxpayer education or equitable enforcement. Contextual factors like financial constraints and social norms further modulate compliance behavior. The study underscores the need for a holistic policy approach, integrating sanctions with educational programs, improved digital services, and tailored incentives to foster voluntary compliance. Practical recommendations include enhancing MSMEs’ tax literacy, ensuring consistent sanction implementation, and optimizing e-filing systems. This synthesis contributes to the tax compliance literature by highlighting the interplay between punitive measures and socio-economic contexts in shaping MSMEs’ fiscal behavior.